Dissertation about the Importance of Aristotelian Philosophy in Heidegger’s Thinking - Mickevičius, Tomas Nemunas (Problemos, 2014)
Doctoral defense of Nerijus Stasiulis.
Keywords: Nerijus Stasiulis; doctoral defense